FACTUAL ACTION AS ADMINISTRATIVE DISPUTES (PROHIBITION OF MISLEADING LAWSUIT BETWEEN THE ADMINISTRATIVE DECISION AND THE FACTUAL ACTION) - David Pasaribu; Istislam; Sudarsono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article attempts to comprehend the ideal concept of factual action and analyzes factual action as an object of dispute in the Administrative Court ("Peratun") in relation to the prohibition of misleading the administrative decision ("KTUN") and the factual action. The research method uses normative research with conceptual, statutory, and case approaches. The results show the complexity of factual action related to examine the factual action and also the double-checking system of administrative tort. First, by classifying an object as the factual action or KTUN, and second, by examining factual actions as the administrative tort by government agencies/officials which are clashing/not clashing to the statutory regulations nor general principles of good governance. Furthermore, the misleading lawsuit can occur when the lawsuit disrupes/reverses the definition of each object, both KTUN and factual actions. The cumulation of objects among KTUN with factual actions is possible as long as there are interrelated legal character (innerlijke samenhang) of objects, prioritize the speedy trial, simple, and low-cost principle, and the principle of utility (bring justice closer to the people).